Novel surface passivation materials towards high efficiency and stability of perovskite solar cells - Foong, Japheth Joseph Yeow Wan (2019)
Being the future of all photovoltaic technology, perovskite solar cells (PSC) has gained an increase in research interest. Its popularity surrounds the direct band gap electronic structure with high absorption coefficient, great photo-physical properties, and tuneable electronic structure by varying species of the ABX3 structure, with versatile low cost fabrication methods. Such great advantages further escalate research interest after reaching performance that is comparable to the mature Silicon Photovoltaic (PV) technologies. However, issues in stabilities remain the biggest challenge restraining the Perovskite PV technologies to be commercialized. Hence, the popular stability improvement technique known as surface passivation has be widely employed and research to troubleshoot stability issues. Generally, 3D perovskite are high in photovoltaic performance but it stability was greatly scarified while the opposite appeal for 2D perovskite. Herein this report, moisture stability improvement of the 3D Methylammonium Lead Iodide (MAPbI3) was demonstrated with the aid of the novel alkylammonium alkynoate molecules with varying aliphatic chains. Demonstrated molecules were Butylammomium Butanoate (C4), Octylammonium Octylanoate (C8) and Hexyldecylammonium Hexyldecanoate (C16). Studies in this report includes the investigation of the optimum concentration and stability effects of different aliphatic chains length in alkylammonium alkynoate. A series of materials and photo-physical characterizations were performed on the control and passivator-treated perovskite films. Even though longer aliphatic chains resulted in higher hydrophobicity shown by the water contact angle, C8 and C16 devices experience catastrophic decease device stability and low photovoltaic performance. A total of 91 cells were fabricated and measured to evaluate the photovoltaic performances. Results demonstrated that C4-treated PSC at 10mM showed the highest improvement photovoltaic performance and the longest device stability over a period of 40 days. The Power Conversion Efficiency (PCE) of best performing device was 16.4% by C4-treated PSC. C4-treated PSC also demonstrated 82.66% retain of its initial PCE after 40 days at 30% RH and 25oC under dark storage conditions.